Assistance in the Development of RBL-STEM Learning Tools Based on AI and IoT to Improve Students' Thinking Skills - Robiatul Adawiyah; Arika Indah Kristiana; Dafik (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
A teacher is an educator who is required to continuously develop his skills and knowledge. Learning today is no longer learning that can be packaged conventionally if the teacher wants good learning outcomes. Current learning must be able to increase students' interest in learning. One type of learning that is currently trending is learning based on artificial intelligence and Internet of things (IoT). The quality of human resources can be seen from the ability of graduates who have skills, master technology, and have extensive knowledge and professional expertise. To improve the digital literacy competency of educators, the Unej service team carries out community service. The training activities carried out aim to increase teacher competency in utilizing AI and IoT as learning media especially in developingRBL-STEM learning tool. The implementation of this training uses the IHT method, lectures and mentoring. As a result, participants were able to create digital learning assisted by AI and IoT. Based on the results of media trials on students based on pretest and posttest, a probability or Sig value was obtained. (2-tailed) is equal to 0.000 with an alpha of 0.05, meaning there is a significant difference between the results on the pretest and posttest. In the posttest results, it was found that students' scores had increased in their thinking abilities.